Strategic Management in Emerging Economies: a Research Agenda - Crittenden, Victoria L.; Crittenden, William F. (Organizations and Markets in Emerging Economies, 2010)
The fragility of the global economy has been evidenced extensively over the past few years. The rapidity at which change can impact worldwide economies has invigorated a major concern in emerging economies. That concern is one of how to play the game when the rules of the game are changing and not completely known. The intent of this research agenda is to fuse early ideas in emerging markets with more recent research from a wide variety of scholars so as to develop a 21st century research agenda for emerging economies. This research agenda offers 20 broad research questions within the emerging economies context, with a major focus on challenges, institutional voids, and growth strategies.
Keywords: boundaryless marketplace; cross-disciplinary; international theory